The Competitiveness of Local Wisdom-Based MSME Products in Facing Global Markets - Bagus Wahzu Ilahi Yusuf (Study Program of Sharia Business Management , Faculty of Islamic Economics and Business, 2025)
This study investigates the competitiveness of local wisdom-based Micro, Small, and Medium Enterprises (MSMEs) in Indonesia within the context of global markets. The research addresses a pressing question: why do culturally rich MSMEs struggle to achieve international competitiveness? Using a qualitative descriptive-analytic method, the study draws on interviews, field observations, and secondary data from MSMEs in Bali, Yogyakarta, and West Sumatra. Porter’s Diamond Model and Cultural Branding Theory serve as analytical frameworks to assess internal capabilities, strategic gaps, and market alignment. The findings show that while 68% of MSMEs incorporate cultural elements in their products, only 33% are globally competitive, and just 22% have reached export markets. Key obstacles include limited branding strategy, lack of international certification, fragmented support infrastructure, and insufficient digital engagement. The study concludes that cultural capital alone is not sufficient; it must be converted into structured competitive strategies to position MSMEs on the global stage.